Biomechanical Responses of the Brain in Swine Subject to Free-Field Blasts - Feng, Ke; Zhang, Liying; Jin, Xin; Chen, Chaoyang; Kallakuri, Srinivasu; Saif, Tal; Cavanaugh, John; King, Albert (Frontiers in Neurology, 2016)
Blast-induced traumatic brain injury (bTBI) is a signature wound of modern warfare. The current incomplete understanding of its injury mechanism impedes the development of strategies for effective protection of bTBI. Despite a considerable amount of experimental animal studies focused on the evaluation of brain neurotrauma caused by blast exposure, there is very limited knowledge on the biomechanical responses of the gyrenecephalic brain subjected to primary free-field blast waves imposed in vivo. This study aims to evaluate the external and internal mechanical responses of the brain against different levels of blast loading with Yucatan swine in free field. The incident overpressure (IOP) was generated using 3.6 kg of C4 charge placed at three standoff distances from the swine. Five swine were exposed to a total of 19 blasts. The three average peak IOP pressure levels in this study were 148.8, 278.9, and 409.2 kPa as measured by a pencil probe. The duration of the first positive wave was in the range of 2.1 - 3 ms. Pressure changes in the brain and head kinematics were recorded with intracranial pressure (ICP) sensors, linear accelerometers and angular rate sensors. The corresponding average peak ICPs were in the range of 79-143, 210-281, and 311-414 kPa designated as low, medium, and high blast level, respectively. Peak head linear accelerations were in the range of 120-412 g. A positive correlation between IOP and its corresponding biomechanical responses of the brain was also observed. This experimental data can be used to validate computer models of bTBI.